2004
DOI: 10.1108/02683940410551534
|View full text |Cite
|
Sign up to set email alerts
|

Trust‐building strategies in inter‐organizational negotiations

Abstract: One challenge for multinational organizations is to manage inter-organizational relationships with customers, collaborators, competitors, governments and other important stakeholder organizations. Negotiations can be seen as a process to manage interdependence and conflicts of interests between parties. As a result, negotiation analysis and theory provide a useful framework to analyze dynamics of relationship-and trust-building and hence are increasingly important for the understanding of inter-organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 65 publications
6
43
0
3
Order By: Relevance
“…On the other hand, from the private sector stakeholders' perception, the results showed that 9 out of the 15 private stakeholders also agreed on this statement (3 out 6 private companies, 2 out of 3 academic and research centers and 4 out of 6 experts).In other words, both the public and private sector interviewees agree that the cooperation between the public and private stakeholders involved in the environmental management in Lebanon is related to trust relations. This result can be confirmed by many scholars (Ferrin et al 2007;Lundin 2007;Edelenbos & Erik-Hans 2007;koeszegi 2004;Parkhe 1993). Thus, based on the public and privates interviewees' perspective, this research claims that building trust relation between the public and private stakeholders is essential for having more cooperation among these multistakeholders and thus having a more successful decisions, developmental plans or environmental projects.…”
Section: What Are the Reasons Behind This Weak Cooperation?supporting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, from the private sector stakeholders' perception, the results showed that 9 out of the 15 private stakeholders also agreed on this statement (3 out 6 private companies, 2 out of 3 academic and research centers and 4 out of 6 experts).In other words, both the public and private sector interviewees agree that the cooperation between the public and private stakeholders involved in the environmental management in Lebanon is related to trust relations. This result can be confirmed by many scholars (Ferrin et al 2007;Lundin 2007;Edelenbos & Erik-Hans 2007;koeszegi 2004;Parkhe 1993). Thus, based on the public and privates interviewees' perspective, this research claims that building trust relation between the public and private stakeholders is essential for having more cooperation among these multistakeholders and thus having a more successful decisions, developmental plans or environmental projects.…”
Section: What Are the Reasons Behind This Weak Cooperation?supporting
confidence: 68%
“…First of all, according to the stakeholders of the public sector 22 out of 34 of the public stakeholders stated that they agree that the cooperation is related to trust relation (15 out of 24 municipalities, 5 out of 7 ministries and 2 out of 3 public institutes). This answer can be confirmed also by many scholars (Ferrin et al 2007;Ferrin et al 2008, p: 168;Koeszegi 2004). Thus, one of the factors that able us to have more cooperation is by working on building more trust.…”
Section: What Are the Reasons Behind This Weak Cooperation?supporting
confidence: 67%
See 1 more Smart Citation
“…Plusieurs recherches ont souligné l'importance de la communication et des échanges d'information pour établir des relations saines (Koeszegi, 2004 ;Gillespie et Mann, 2004 ;Lewicki et Bunker, 1996 ;Roberts et O'Reilly, 1974), et rebâtir la confiance cognitive. Le simple fait de communiquer n'est pas suffisant.…”
Section: Analyse Des Facteurs Communs Soulevésunclassified
“…Ceci doit se faire fréquemment en face à face pour permettre la discussion et l'échange d'information au sujet des besoins, désirs et perspectives de résolutions de problèmes (Lewicki et Bunker, 1996). Ces échanges amélioreront la qualité de la relation (Koeszegi, 2004) et répondront au besoin privilégié des cadres et des employés (Harrisson, 2003). À la fréquence, s'ajoutent aussi le message authentique et sans déformation (Mishra, 1996), la perception de la satisfaction de la communication (Clampitt et Downs, 1993) et le contenu des informations.…”
Section: Analyse Des Facteurs Communs Soulevésunclassified